2005
DOI: 10.1021/la051272o
|View full text |Cite
|
Sign up to set email alerts
|

PtRu/Carbon Nanotube Nanocomposite Synthesized in Supercritical Fluid:  A Novel Electrocatalyst for Direct Methanol Fuel Cells

Abstract: Platinum/ruthenium nanoparticles were decorated on carbon nanotubes (CNT) in supercritical carbon dioxide, and the nanocomposites were characterized by transmission electron microscopy (TEM) and X-ray diffraction (XRD). TEM images show that the particles size is in the range of 5-10 nm, and XRD patterns show a face-centered cubic crystal structure. Methanol electrooxidation in 1 M sulfuric acid electrolyte containing 2 M methanol were studied onPtRu/CNT (Pt, 4.1 wt%; Ru, 2.3 wt%; molar ratio approximately Pt/R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
177
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(191 citation statements)
references
References 63 publications
11
177
1
2
Order By: Relevance
“…For PtRu on CNT support neither here nor previously [150] has reported any shift. Furthermore, with PtRu/FWCNT an additional feature appears in the oxide formation region (0.55 V) that is observed also in Figure 27 and is related to the acid treatment reported previously by other groups [150][151][152]. This feature have been reported only on CNTs and not on GNFs even though they have both been acid treated, indicating that different surface groups are formed on each support.…”
Section: Support Materialssupporting
confidence: 78%
“…For PtRu on CNT support neither here nor previously [150] has reported any shift. Furthermore, with PtRu/FWCNT an additional feature appears in the oxide formation region (0.55 V) that is observed also in Figure 27 and is related to the acid treatment reported previously by other groups [150][151][152]. This feature have been reported only on CNTs and not on GNFs even though they have both been acid treated, indicating that different surface groups are formed on each support.…”
Section: Support Materialssupporting
confidence: 78%
“…The R ct values of the nanocatalysts are estimated by fitting the EIS curves using the software ZsimpWin based on an equivalent electric circuit as shown inset of Figure 8. 78 In this R s (R ct CPE) circuit, R s represents the uncompensated solution resistance, R ct represents the charge-transfer resistance while the constant phase element (CPE) is related to a capacitor property, The parallel combination of the R ct and CPE takes into account the thin electrode film as well as ethanol adsorption and oxidation. The values for all the parameters R s , R ct , CPE and their associated % error are summarized in Table III.…”
Section: Ec S a = Q/slmentioning
confidence: 99%
“…In order to enhance catalytic activity and to reduce the usage of Pt-based catalysts, one strategy is to explore novel carbon materials as catalyst supports and to effectively disperse Pt-based particles on these supports (Chen et al, 2007;Sanganna Gari et al, 2010;Girishkumar et al, 2006;Halder et al, 2009;Maiyalagan, 2008;Selvaraj & Alagar, 2007;Rajesh et al, 2003;Tang et al, 2004;Tsai et al, 2006;Zhao et al, 2004). Vulcan XC-72R carbon black has been the most widely-used catalyst support for the preparation of fuel cell catalysts because of its exceptional electronic conductivity and surface area (Guo et al, 2008;Lin et al, 2005;Maiyalagan et al, 2005). During the past several years, a few research groups have investigated graphene, one type of novel carbon nanostructures, as a catalyst support and have demonstrated that graphene can improve the electrocatalytic activity of Pt nanoparticles more effectively for methanol and ethanol oxidation than Vulcan XC-72R carbon black Seger et al, 2009;Yoo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%